Dose-dependent effect of chronic exposure to lead acetate on the dynamics of the content of delta-aminolevulinic acid and essential trace elements in the serum of laying hens - Dotsenko, E.; PaliyА.; Morozenko, D.; Dotsenko, R.; ZemlianskyiА.; Pavlichenko, O. (Regulatory Mechanisms in Biosystems, 2021)
One of the most global and dangerous pollutants is considered to be lead, due to its ability to accumulate in living organisms, to be included in the metabolic cycle, to form highly toxic organometallic compounds, not being biodegradable. To study the chronic effects of lead acetate, an experiment was performed on laying hens of Lohmann Brown cross. For research, one control and three experimental groups were formed, 20 chickens in each. Birds of the experimental groups were administered lead acetate daily with compound feed in doses (in terms of metal): Group I – 50 mg/kg of feed, II – 75 mg/kg of feed, III – 150 mg/kg of feed. Access to water was not restricted. The birds of the control group received a complete diet without lead acetate. On the 30th, 90th, 120th days of the experiment and the 20th day after withdrawal of the toxicant (the 140th day of the experiment), we took blood samples from birds for biochemical and toxicological studies. The concentration of delta-aminolevulinic acid (δ-ALA) in the serum of laying hens was determined by reversed-phase high-performance liquid chromatography. Determination of the content of lead in the serum of laying hens was performed by X-ray fluorescence analysis. The concentration of total calcium, inorganic phosphorus, and magnesium in the serum of the laying hens was determined using production kits. We detected the dose-dependent chronic effect of lead acetate on the dynamics of the content of delta-aminolevulinic acid and essential trace elements in the serum of laying hens. The administration of lead acetate into the body of productive poultry for 120 days in doses of 50, 75, and 150 mg/kg with feed did not cause visible clinical signs of poisoning, but caused a violation of porphyrin metabolism, manifested in a reliable increase in the concentration of delta-aminolevulinic acid in serum on the 30th, 90th and 120th days of the experiment. It has been experimentally proven that the administration into the body of laying hens of lead acetate in doses of 50, 75 and 150 mg/kg of feed for 120 days leads to the maximum accumulation of lead in the serum on the 30th, 90th, and 120th days of the experiment. Prolonged administration of lead acetate to laying hens at high concentrations is characterized by a reliable decrease in the content of total calcium, inorganic phosphorus and magnesium in the serum of laying hens and a reliable increase in the content of ferrum. In the future it is necessary to study the intensity of lipid peroxidation processes in laying hens under chronic exposure to lead acetate.